PHARMACEAUTICAL CARE IMPROVED THE QUALITY OF LIFE OF PATIENT WITH HEMODIALYSIS - LUBIS, ASYRUN ALKHAIRI; NASUTION, AZIZAH; ROSIDAH (International Journal of Current Pharmaceutical Research, 2019)
Objective: Patients undergoing hemodialysis in the long term often experience complications that affect the quality of life (QOL) of the patients. Comprehensive health services are very important for improving the QOL of the patients with chronic renal failure undergoing hemodialysis. The purpose of this study was to prove that the provision of therapy with pharmaceutical care can improve the QOL of hemodialysis patients. Methods: This research was a quasi-experimental study pre and post test design. Samples were recruited applying the purposive sampling method. As many as 50 patients met the inclusion criteria and were asked to fill out the World Health Organization Quality Of Life (WHOQOL) questionnaire to measure their QOLs before and after the provisions of pharmaceutical care. Data obtained before and after pharmaceutical care were tested using paired t test, person correlation test, and Wilcoxon test in the program of SPSS 19. Results: The results showed women more often experience complications when hemodialysis (62%), sex with quality of life (p = 0.907), education with quality of life (p = 0.277), work with quality of life (p = 0.582) length of undergoing hemodialysis with quality life (p = 0.733) no significant effect. Age (p = 0.044) significantly influences quality of life. And the average quality of life before administration of pharmacy and care was 48.12±5.98, while the quality of life after administration of therapy with pharmaceutical care was 50.16±6.22. Based on the Wilcoxon test, this value was significantly different (p = 0.009). Conclusion: The conclusion of this study is the provision of therapy accompanied by pharmaceutical care significantly improves the quality of life of hemodialysis patients.